2013
DOI: 10.1021/ol400016c
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of 3a,6a-Dihydrofuro[2,3-b]furans via a Novel Bicyclization

Abstract: A highly efficient method for the construction of 3a,6a-dihydrofuro[2,3-b]furan derivatives has been developed via a novel bicyclization, which is very valuable for the synthesis of fused furofuran compounds since it is time-saving and catalyst-free. Based on the bicyclization, a coupled domino strategy has been developed to directly construct 3a,6a-dihydrofuro[2,3-b]furan derivatives from methyl ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 30 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…Among bicyclic acetals, FF derivatives are of special interest, since their biological and pharmaceutical activities are known [26]; however, their role as antitumor compounds is still controversial and needs to be elucidated [27]. The DHFF unit is an important skeletal structure in various biologically and pharmaceutically active organic molecules and it is very useful for organic transformations to potential bioactive molecules [28]. As the isolation or the preparation of different types of FF lignans is difficult, the analysis of the relationship between the FF ring, its conjugates, and the established clinical activities has not been done yet [20,29,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Among bicyclic acetals, FF derivatives are of special interest, since their biological and pharmaceutical activities are known [26]; however, their role as antitumor compounds is still controversial and needs to be elucidated [27]. The DHFF unit is an important skeletal structure in various biologically and pharmaceutically active organic molecules and it is very useful for organic transformations to potential bioactive molecules [28]. As the isolation or the preparation of different types of FF lignans is difficult, the analysis of the relationship between the FF ring, its conjugates, and the established clinical activities has not been done yet [20,29,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…A proposed mechanism for the formation of compound 4a is shown in Scheme 8e,11. Initially, arylglyoxal monohydrate 2 undergoes a Knoevenagel condensation with malononitrile to produce α,β‐unsaturated nitrile intermediate 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature reports (Shu et al, 2013) 105 and the results obtained from this domino process, the proposed mechanism is illustrated in Scheme 11 which starts with the addition of aniline 45 to alkyne 46 Furthermore, density functional theory (DFT) calculations were performed at the B3LYP/6-31G level of theory for intermediates 53 and 54 and the results suggested that intermediate 54 could be easily transformed into the more stable pyrrole product 48.…”
Section: Aliya Ibrarmentioning
confidence: 99%